Direct Transfer of Magnetic Sensor Devices to Elastomeric Supports for Stretchable Electronics. (14th January 2015) - Melzer, Michael; Karnaushenko, Daniil; Lin, Gungun; Baunack, Stefan; Makarov, Denys; Schmidt, Oliver G.
<x xml:space="preserve">Abstract</x> A novel fabrication method for stretchable magnetoresistive sensors is introduced, which allows the transfer of a complex microsensor systems prepared on common rigid donor substrates to prestretched elastomeric membranes in a single step. This direct transfer printing method boosts the fabrication potential of stretchable magnetoelectronics in terms of miniaturization and level of complexity, and provides strain‐invariant sensors up to 30% tensile deformation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>